Guideline to Revive the Traditional Wholesale from Economic Recession (Journal of Namibian Studies : History Politics Culture, 2023)
Wholesale business is an economic activity that involves a broad population and plays a vital role in the Thai economy. This research aims to study methods for reviving traditional wholesale businesses from an economic recession. Conducted qualitative and quantitative research, a quantitative survey of 500 business executives registered with the Department of Business Development who profited from operations. Descriptive statistics, reference statistics, and multivariate statistics were used. The priority of five aspects of statistics is listed as follows:1) Logistics Excellence (X ̅ = 4.59) The most important in each item is to provide distribution locations near the production source. 2) Trade Partners (X ̅ = 4.48) The most important in each item is agreements with partners to deliver products using intermediaries such as Grab, FedEx, DHL, Kerry, and Thailand Post. 3) Cost Reduction (X ̅= 4.42) The most important items were financial management plans to find funds from sources suitable for using funds for each type of wholesale business. 4) Digital Technology (X ̅ = 4.37), the most important item is to plan for electronic communication and public relations, cover services, and reach all groups of customers through electronic communication channels. 5) Organizational Reengineering (X ̅= 4.34), the most important in each item was that personnel at all levels jointly set business goals for the organization, as for the results of the hypothesis test. It was found that the type of wholesale consumption of consumer goods paid more attention to the guidelines to revitalize the traditional wholesale business from the economic crisis, and there was no significant difference at the level of 0.05. The developed structural equation model analysis revealed that it passed the evaluation criteria and was consistent with empirical data. The chi-squared probability value was 0.054, the relative chi-squared value was 1.112, the goodness-of-fit index was 0.943, and the root mean squared index of the error estimate was 0.015.